Soluble NSF attachment protein receptor molecular mimicry by a Legionella pneumophila Dot/Icm effector. (24th January 2015) - King, Nathan P.; Newton, Patrice; Schuelein, Ralf; Brown, Darren L.; Petru, Marketa; Zarsky, Vojtech; Dolezal, Pavel; Luo, Lin; Bugarcic, Andrea; Stanley, Amanda C.; Murray, Rachael Z.; Collins, Brett M.; et al.
Summary Upon infection, Legionella pneumophila uses the Dot/Icm type IV secretion system to translocate effector proteins from the Legionella‐containing vacuole (LCV) into the host cell cytoplasm. The effectors target a wide array of host cellular processes that aid LCV biogenesis, including the manipulation of membrane trafficking. In this study, we used a hidden Markov model screen to identify two novel, non‐eukaryotic soluble NSF attachment protein receptor (SNARE) homologs: the bacterial Legionella SNARE effector A (LseA) and viral SNARE homolog A proteins. We characterized LseA as a Dot/Icm effector of L. pneumophila, which has close homology to the Qc‐SNARE subfamily. The lseA gene was present in multiple sequenced L. pneumophila strains including Corby and was well distributed among L. pneumophila clinical and environmental isolates. Employing a variety of biochemical, cell biological and microbiological techniques, we found that farnesylated LseA localized to membranes associated with the Golgi complex in mammalian cells and LseA interacted with a subset of Qa‐, Qb‐ and R‐SNAREs in host cells. Our results suggested that LseA acts as a SNARE protein and has the potential to regulate or mediate membrane fusion events in Golgi‐associated pathways.